2023
DOI: 10.3390/nu15030483
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin B and Obesity in Middle-Aged and Older Chinese Adults

Abstract: Objective: Previous studies have found that obese people have lower levels of vitamin B, but most have focused on obesity as defined by body mass index (BMI), and its relationship with other types of obesity is unclear. The aim of this study was to explore the relationship between vitamin B levels and obesity assessed by different definitions among Chinese middle-aged and older community-dwelling adults. Methods: This cross-sectional study included 887 participants aged 45 years and older (45–82 years). The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…(3) SLC25A19 . The protein encoded by the SLC25A19 gene was a member of the solute carrier family and was involved in vitamin B 1 metabolism process, while the vitamin B 1 level was reported to be negatively related to obesity (Fu et al, 2023). Moreover, the vitamin B 1 deficiency was also related to some cardiovascular traits, such as elevated cardiac stroke volume, decreased vascular resistance, and elevated pressor responses, suggesting a possible role in influencing BP levels (DiNicolantonio et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(3) SLC25A19 . The protein encoded by the SLC25A19 gene was a member of the solute carrier family and was involved in vitamin B 1 metabolism process, while the vitamin B 1 level was reported to be negatively related to obesity (Fu et al, 2023). Moreover, the vitamin B 1 deficiency was also related to some cardiovascular traits, such as elevated cardiac stroke volume, decreased vascular resistance, and elevated pressor responses, suggesting a possible role in influencing BP levels (DiNicolantonio et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that blood releases a significant amount of ionized Mg 2+ during coagulation; therefore, the concentration of whole-blood magnesium detected using dry blood spots was lower than that in the serum [ 27 ]. Although, DBS-LC-MS/MS has been used specifically to store and measure a variety of minerals, including magnesium [ 28 , 29 ], and previous studies have proved the accuracy of DBS-LC-MS/MS [ 30 , 31 ]. Whether the above explanations are the reasons for the difference in study results still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a recent meta-analysis by Eitmann et al demonstrated that the age-dependent impact of additional obesity on all-cause mortality in sarcopenic people results in lower mortality risk in older adults, i.e., the obesity paradox [ 91 ]. It has been reported that circulating B6 levels were negatively related to obesity in middle-aged and older adults [ 92 , 93 ]. Additionally, B6 status in obese adults was positively associated with health consequences [ 17 , 34 ].…”
Section: Outlook For Future Researchmentioning
confidence: 99%